PENGARUH UKURAN PERUSAHAAN, PERATAAN LABA, DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK - Deded Deded; Ruhul Fitrios Ruhul Fitrios; Oktari Vera (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research aims to analyze the impact of company size, income smoothing, and profitability on tax avoidance,.The population in this research is company listed in Indonesia Stock Exchnage in 2017 until 2019. Total sample in this research is 66 companies with three years observation. Sampling technique in this research using purposive sampling technique and analysis teqhnique using multiple liniear regression The result of this research indicates that Company Size, Income Smoothing, and Profitability have no significant impact on tax avoidance.Keywords: Company Size, Income Smoothing, Profitability, Tax Avoidance.